PROFITABILITY, FIRM SIZE, AND FINANCIAL REPORTING TIMELINESS: AUDIT FIRM REPUTATION AS A MODERATOR - Mohammad Akbar Dwi Ferdianto; Rida Perwita Sari (Universitas Tulungagung, 2026)
This study aims to examine the effect of profitability and firm size on financial reporting timeliness, with Public Accounting Firm (KAP) reputation as a moderating variable. A quantitative approach was employed with a population of property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Through purposive sampling, a valid sample of 48 companies with 240 observations was obtained. Data analysis was conducted utilizing Partial Least Squares - Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0 software. The results indicate that profitability and firm size have a significant effect in accelerating the timeliness of financial reporting. However, testing of the moderating variable reveals that KAP reputation does not moderate the effect of profitability and firm size on reporting timeliness. These empirical findings corroborate signaling theory and agency theory, affirming that the efficiency of audit completion time is predominantly driven by internal motivation and administrative readiness, rather than a reliance on Big Four KAP affiliations.